Implementation of Radha'ah's Card as Alternative Care of Nasab and Babies with Breastfeeding by Selangor Islamic Religious Department: (Pelaksanaan Kad Radha'ah sebagai Alternatif Penjagaan Nasab Keturunan dan Anak Susuan oleh Jabatan Agama Islam Selangor) (Kanun: Jurnal Undang-undang Malaysia, 2020)
This qualitative study is an analysis following the implementation of the MyRadha'ah Card which was introduced in Malaysia by the Selangor Islamic Religious Department (JAIS) on 19 November, 2018. It is a mechanism for ascertaining the identity of a child and its wet nurse or 'milk- mother'. This aids in safeguarding the Islamic family institution, in particular, involving nasab (lineage) and mahram (unmarriageable kin) to manifest the Maqasid Shariah (objectives of the sharia) which requires hifz al-nasl or care of the offspring. This study, therefore, is meant to study the concept of wet-nursing from the point of view of Islamic law, as well as identifying the institutions or agencies that should play a role in regulating issues related to wet-nursing. The data were obtained through library research and interviews analysed using inductive and deductive methods. The study finds that the implementation of the MyRadha'ah Card should not be limited to one state but is a necessity for the entire country. The cooperation of various parties is crucial for implementation in stages and requires streamlining among all the states in Malaysia.Keywords: MyRadha'ah Card, nasab, hifz al-nasl, wet-nursing, milk kinship